Effects of alpha-lipoic acid on serum inflammatory factors and nutritional parameters in ESRD patients receiving hemodialysis - LIU Fei (Linchuang shenzangbing zazhi)
Objective To study the effects of alpha-lipoic acid on serum inflammatory factors,and nutritional parameters in end-stage renal disease(ESRD)patients receiving hemodialysis.Methods A total of 68 patients with ESRD undergoing hemodialysis in our hospital from September 2013 to September 2015 were recruited in our study and randomly divided into control group(n=34)and observation group(n=34).The control group received routine ESRD treatment and hemodialysis,while the observation group received alpha-lipoic acid treatment additionally on the basis of routine treatment.The serum levels of inflammatory factors(hs-CRP,IL-6,IL-8,TNF-α),nutritional parameters(Hb,Alb,TC,TG,HDL-C and LDL-C),as well as serum Hcy,PTH,β2-MG in the two groups before and after treatment were collected and compared.Results After treatment,the serum levels of hs-CRP,IL-6,IL-8 and TNF-αin the two groups were significantly lower than those before treatment,and those were decreased more significantly in the observation(P<0.05).After treatment,serum Hb and Alb levels were significantly increased as compared with those before treatment(P<0.05),and those were significantly higher in the observation group than those in the control group(P<0.05).The serum TC,TG,HDL-C and LDL-C levels had no significant change(P>0.05).There were no significant differences in the above indexes of the control group before and after treatment(P>0.05).There was no statistically significant difference in serum TC,TG,HDL-C and LDL-C levels between the two groups after treatment(P>0.05).After treatment,the serum levels of Hcy,PTH and beta 2-MG in the two groups were significantly lower than those before treatment,more significantly in the observation group than in the control group(P<0.05).Conclusions Alphalipoic acid used in ESRD patients receiving hemodialysis can effectively reduce the inflammation of kidney,improve the nutritional status of patients,and increase the clearance of Hcy,PTH andβ2-MG,which has good clinical value and worthy of promotion.